Personal Motivation and Satisfaction to School Leaders Among Elementary Teachers: Correlation and Regression Approach - Casinillo, Leomarich F; Hungo, Melbert; Cortes, Jessica; Bijo S. Anand (Jurnal Pendidikan Indonesia, 2024)
Many teachers experience decreased motivation and dissatisfaction due to a lack of support from school leaders, which ultimately impacts the quality of teaching and learning. This study analyzes the relationship between teachers' motivation and satisfaction with school leadership using correlational and regression approaches. This study used a quantitative descriptive-correlational research design. Sixty-one primary school teachers participated in this study as respondents, who were selected through simple random sampling. Data were collected using a validated research questionnaire consisting of motivation and satisfaction. The research instrument was subjected to a reliability test with Cronbach's alpha to ensure consistency using the instrument in the form of a questionnaire sheet. Data analysis used descriptive statistics, Pearson product-moment correlation, Spearman rho correlation, chi-square test, ordinary least square (OLS) regression, and logit regression to determine the strength and direction of the relationship between variables. The regression results further showed that increased satisfaction with school leadership predicted higher levels of teacher motivation. It is concluded that improving school leadership practices can significantly contribute to increased teacher motivation, improving teaching quality and overall school performance. Therefore, it is recommended that school leaders receive targeted training to develop leadership skills that can increase teacher satisfaction and motivation.